Proposed North Atlantic lease offering, April 1984 : United States Department of the Interior final environmental impact statement - United States. Minerals Management Service. Atlantic OCS Region. (Vienna, VA : The Region, 1983)
Index and 5 col. maps on folded sheets issued in envelopes. Spine title: North Atlantic April 1984 lease offering : final environmental impact statement. Cover title: Proposed April 1984 North Atlantic Outer Continental Shelf oil and gas lease offering : final environmental impact statement. Bibliography: p. 577-619. Mode of access: Internet.